Ghost Doctors : Absenteeism in Bangladeshi Health Facilities - Chaudhury, Nazmul; Hammer, Jeffrey S. (World Bank, Washington, DC, 2014)
The authors report on a study in which unannounced visits were made to health clinics in Bangladesh with the intention of discovering what fraction of medical professionals were present at their assigned post. This survey represents the first attempt to quantify the extent of the problem on a nationally representative scale. Nationwide the average number of vacancies over all types of providers in rural health centers is 26 percent. Regionally, vacancy rates (unfilled posts) are generally higher in the poorer parts of the country. Absentee rates at over 40 percent are particularly high for doctors. When separated into level of facility, the absentee rate for doctors at the larger clinics is 40 percent, but at the smaller sub-centers with a single doctor, the rate is 74 percent. Even though the primary purpose of this survey is to document the extent of the problem among medical staff, the authors also explore the determinants of staff absenteeism. Whether the medical provider lives near the health facility, access to a road, and rural electrification are important determinants of the rate and pattern of staff absentee rates.